Gut microbiome and aging: Physiological and mechanistic insights - Yadav, Hariom; Marotta, Francesco; Kushugulova, Almagul; Kitzman, Dalane W.; Kavanagh, Kylie; Singh, Ria; Wang, Shaohua; Ahmadi, Shokouh; Mainali, Rabina; Nagpal, Ravinder; Nagpal, Ravinder (SAGE Publications, 2017)
The development of human gut microbiota begins as soon as the neonate leaves the protective environment of the uterus (or maybe in-utero) and is exposed to innumerable microorganisms from the mother as well as the surrounding environment. Concurrently, the host responses to these microbes during early life manifest during the development of an otherwise hitherto immature immune system. The human gut microbiome, which comprises an extremely diverse and complex community of microorganisms inhabiting the intestinal tract, keeps on fluctuating during different stages of life. While these deviations are largely natural, inevitable and benign, recent studies show that unsolicited perturbations in gut microbiota configuration could have strong impact on several features of host health and disease. Our microbiota undergoes the most prominent deviations during infancy and old age and, interestingly, our immune health is also in its weakest and most unstable state during these two critical stages of life, indicating that our microbiota and health develop and age hand-in-hand. However, the mechanisms underlying these interactions are only now beginning to be revealed. The present review summarizes the evidences related to the age-associated changes in intestinal microbiota and vice-versa, mechanisms involved in this bi-directional relationship, and the prospective for development of microbiota-based interventions such as probiotics for healthy aging.